International mechanisms for the settlement of international environmental disputes - Toufik, Bouki; Fouad, Gueddouri (Art Law and Accounting Reporter, 2025)
Transboundary environmental disputes have witnessed a notable increase with the escalation of challenges arising from marine pollution and activities harmful to the marine environment. This development necessitates the activation of peaceful settlement mechanisms that strike a balance between states’ interests and sovereignty on the one hand, and the protection of the shared environment on the other. This study seeks to analyze the international mechanisms available under the 1982 United Nations Convention on the Law of the Sea (UNCLOS), distinguishing between non-judicial mechanisms (negotiation, mediation, conciliation) in the first section, and judicial mechanisms (the International Court of Justice, the International Tribunal for the Law of the Sea, and arbitration) in the second section. The study aims to assess their adequacy and effectiveness in addressing the central question: to what extent do these mechanisms achieve a balance between state sovereignty and the protection of the marine environment?